PENGARUH TERAPI MUROTTAL AL-QUR’AN TERHADAP PENURUNAN INTENSITAS NYERI PADA INPARTU KALA 1 FASE AKTIF DI PMB MEDITA KEDUNGDUNG - Zulfa , Ummu; Sulistiyah (Institut Kesehatan dan Teknologi Al Insyirah, 2025)
Childbirth pain is a typical aspect of the delivery process and is often regarded as an unwelcome experience due to the mother's increased stress levels and the physical agony endured. This pain arises from uterine contractions that lead to the dilation and thinning of the cervix, as well as uterine ischemia stemming from the contractions of the myometrial arteries. Intense pain can trigger anxiety, which may in turn promote the production of prostaglandin hormones. Strategies to alleviate labor pain can be categorized into pharmacological methods (utilizing medication) or non-pharmacological approaches (employing non-drug techniques such as massage, physical touch, or listening to music). This research was designed as a pre-experimental study with a one-group pre-test and post-test framework. The study population consisted of all mothers who delivered at PMB Medita Kedungdung, with a sample size of 25 mothers selected through accidental sampling, adhering to inclusion criteria. Pain assessment was conducted using a behavioral observation sheet utilizing a Numeric Rating Scale (NRS). The hypothesis test applied is Wilcoxon with a value (p value < 0.05). The results of the statistical analysis show a p value < 0.001, indicating a significant effect between the measurements before and after the introduction of murottal Al-Qur'an therapy in reducing labor pain during the initial active phase. It is advisable to implement non-pharmacological strategies to manage labor pain for mothers in labor at PMB Medita Kedungdung.